From Extraction to Partnership: Epistemic Injustice and the Institutionalization of Research Practices in Nigerian Social Science - Thomas Ogar; George Aboka; Paalee Fidelis (Universitas Negeri Makassar, 2025)
This paper presents a comprehensive philosophical examination of how epistemic injustice becomes embedded within the institutional architecture of social scientific research, using Nigeria as a paradigmatic case study. Moving beyond Miranda Fricker's foundational framework, we argue that epistemic injustice in postcolonial research contexts operates not merely as interpersonal ethical failure but as systematically reproduced structural violence enabled by what we term “epistemic extraction regimes.” Through detailed analysis of Nigeria's research ecosystem, encompassing ethics review boards, funding mechanisms, methodological protocols, and knowledge dissemination practices, we demonstrate how testimonial and hermeneutical injustices become normalized through institutional procedures that privilege Northern epistemological frameworks while marginalizing indigenous knowledge systems. The paper develops the original concepts of “hermeneutical foreclosure” and “testimonial instrumentalization” to describe how institutional practices actively preclude alternative ways of knowing. Drawing extensively from Nigerian philosophical traditions, including Yoruba epistemology, Igbo metaphysical systems, and contemporary African philosophical discourse, We propose a radical reimagining of social research grounded in what we call “epistemic consociation”, a framework for knowledge production that honors epistemological pluralism while maintaining rigorous scholarly standards. The argument contributes to both social epistemology and philosophy of social science by demonstrating how institutional structures actively constitute, rather than merely mediate, epistemic relations in postcolonial research contexts.